Pulmonary Function Status Following Long Term Fiberglass Dust Exposure in Orthopaedic Clinic - Zulkifli Abu Bakar, Dr. Irman Abdul Rahman, Dr. Anuar Ithnin, Dr. Amaramalar Selvi Naicker, Dr. Samhani Ismail (Drugs and Cell Therapies in Hematology, 2021)
Background: This study aimed to investigate pulmonary function performance among healthcare workers (HCWs) occupationally exposed to fiberglass dust materials and the association with the duration of the year of employment. Methods: A cross-sectional study was conducted by recruiting 99 HCWs exposed to fiberglass and 107 unexposed workers (i.e. reference group) from five orthopedic clinics in Malaysia. A standardized respiratory questionnaire was used and the subjects underwent pulmonary function tests during working hours. To assess the degree of pulmonary function status following the exposure to fiberglass dust, environmental and personnel air sampling were measured in different work stations using standard methods. Results: The age of the majority (31.3%) of exposed subjects ranged from 31 to 35 years and 32.3% of them had a duration of exposure between 1 to 5 years. The mean cumulative concentration of fiberglass dust in the workstation Plaster of Paris (POP) room for personnel sampling (1.63 fibre/cc) and area sampling (2.17 fibre/cc) were 1 and 2 times, respectively above the permissible exposure limit. The pulmonary function test showed a significant decrease in the mean values of FVC, FEV1, and %FEV1/FVC ratio with the age, gender, and duration of employment for the exposed group. Conclusion: It is assumed that healthcare workers in the orthopedic clinic are at increased risk of developing occupational-related pulmonary impairment. Here we recommend the obligatory use of the standard regulatory personal protective equipment, particularly for the HCWs in the POP room.